The relationship between matrix metalloproteinases (MMP-3, -8, -9) in serum and peripheral lymphocytes (CD8+, CD56+) in Down syndrome children with gingivitis - Tsilingaridis, G.; Yucel-Lindberg, T.; Concha Quezada, H.; Modéer, T. (Journal of periodontal research, 2014)
Background and Objective Altered immune response may be a major contributor to periodontal disease in Down syndrome. This study investigated the relationship between peripheral lymphocytes and matrix metalloproteinases (MMPs) in serum in Down syndrome children with gingivitis. Material and Methods Children with Down syndrome (n = 10) and healthy controls (n = 10) were clinically and radiographically examined during dental treatment under general anaesthesia. Peripheral blood and gingival crevicular fluid were collected from each subject and concentrations were determined: serum MMP‐2, ‐3, ‐8 and ‐9; serum tissue inhibitors of metalloproteinases (TIMP) ‐1, ‐2 and ‐3; and gingival crevicular fluid. Leukocytes were isolated from peripheral blood and the relative amounts (%) of the various cell phenotypes were analysed using flow cytometry. In addition, peripheral blood cells were treated with Porphyromonas gingivalis lipopolysaccharide and levels of MMPs and TIMPs measured. Results Concentrations of MMP‐3, MMP‐8 and TIMP‐1 in serum were significantly higher (p < 0.05) in the Down syndrome group compared to the controls. When peripheral blood leukocytes were cultured in the presence or absence of P. gingivalis lipopolysaccharide, MMP‐8 levels were significantly (p < 0.05) higher in the Down syndrome group compared to controls. Children with Down syndrome exhibited significant positive correlations between CD8+ T cells and MMP‐8 (r = 0.630; p = 0.050), between CD8+ T cells and MMP‐9 (r = 0.648; p = 0.043), and between CD56+ NK cells and MMP‐3 (r = 0.828; p = 0.003) compared to controls. Conclusions The positive relationship of serum MMP‐3, ‐8 and ‐9 with immune cells in children with Down syndrome may facilitate migration of CD8+ T cells and CD56+ NK cells into the periodontal tissue, which may contribute to the increased degradation of periodontal tissue in individuals with Down syndrome.